Hidup dan Pelayanan Yesus Sebagai Landasan Pendidikan Kristiani - Sarah Wassar (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
Christian education lessons are held at home, church, and school. The importance of Christian education can be seen in the life and ministry of Jesus Christ while he was on earth. The Bible is the basis of Christian education, which guides believers to know the person, life, and ministry of Jesus as a reality for the foundation of Christian education so that Christians can carry out the task of the great commission of the Lord Jesus, (Matt. 28: 19-20) namely to make disciples of all nations and teach them to do everything that the Lord Jesus commanded. This research was conducted using qualitative methods, namely library or literature study in the form of theological analysis as a basis for conducting biblical Christian education learning.